Risk factors of osteoarthritis that reduce the Steinbrocker’s functional capacity of patients with osteoarthritis of the knee - Bambang Setiyohadi; A R Nasution; H Isbagio (Indonesian Journal of Rheumatology, 2009)
Objective. This study was implemented to determine the risk factors of osteoarthrosis which potentially could reduce the Steinbrocker’s functional capacity (SFC) of patients with osteoarthrosis of the knee.Method. In this cross sectional study, the cases were taken consecutively from the ambulatory patient with the osteoarthrosis of the knee who visited the rheumatologyclinic, Cipto Mangunkusumo Hospital. Subjects was interviewed to record the existing and severity risk factors using a structured questionnaire regarding their age, gender, duration of the illness pattern of smoking history of diabetes mellitus, menopause, body mass index (BMI), knee joint deformity, 15 meters walking time and KellgrenLawrence radiologic index.Results. One hundred thirteen cases of osteoarthrosis of the knee were assigned to the study between July to December 1992, 24 patients were male and 89 werefemale. Eighteen patients were designated to SFC I, 77 patients to SFC II, 14 patients to SFC III and 4 patients to SFC IV. With the logistic regression analysis, it was found that the signifi cant risk factors of developing SFC II, III and IV from patients of SFC I were being female and smoking. In the second logistic regression analysis we found that the signifi cant risk factors for developing SFC III and IV from patients of SFC I and II were age and BMI.Conclusion. In this study we have found that age, smoking, female genders, and BMI were the risk factors which potentially could reduce the SFC of patients withosteoarthrosis of the knee.